Resin material, compatibilizer, multilayer structure and multilayer structure recycling method
Patent Information
- Application Number
- JP2023125273
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0007】 本発明によれば、多層構造体の回収性を改善することができる樹脂材料及び相容化剤、並びに回収性が改善された多層構造体及び多層構造体の再利用方法を提供できる。
Smart Images

Figure 2025021523000001 
Figure 2025021523000002 
Figure 2025021523000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin material, a compatibilizer, a multilayer structure, and a method for recycling a multilayer structure. [Background technology]
[0002] Thermoplastic resins such as polyolefins and polystyrenes are widely used in films, sheets, bottles, cups, and other molded products due to their excellent melt moldability, secondary processability, mechanical properties, and economical efficiency. Multilayer structures of these resins and ethylene-vinyl alcohol copolymers (hereinafter also referred to as "EVOH") are widely used in the food industry and other fields where barrier properties against oxygen, water vapor, flavors, and the like are required. Such multilayer structures include those having a layer structure in which an adhesive resin layer is provided between each resin layer. Patent Document 1 describes a multilayer structure in which an EVOH layer having an ethylene unit content of 20 to 60 mol% and a saponification degree of 90% or more and a polypropylene resin layer are laminated via an adhesive resin layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-58374 A Summary of the Invention [Problem to be solved by the invention]
[0004] When manufacturing a molded product made of a multilayer structure having a thermoplastic resin layer, an adhesive resin layer, etc., defective products, punching waste, burrs, etc. are generated. These may be collected, melt-molded, and reused as one of the layers of the multilayer structure. Such recovery and reuse technology is useful in terms of waste reduction and economic efficiency, and has been widely adopted. However, the layer obtained by melt-molding the recovered resin (hereinafter also referred to as the "recovered layer") may have insufficient appearance and quality due to the occurrence of spots called fish eyes, low transparency, etc.
[0005] The object of the present invention is to provide a resin material and a compatibilizer capable of improving the recoverability of a multilayer structure, a multilayer structure having improved recoverability, and a method for reusing the multilayer structure. In this specification, "recoverability" refers to a property that enables a high-quality recovered layer to be formed when the multilayer structure is recovered and melt-molded for reuse, specifically, a property that enables a recovered layer with few fisheyes and high transparency to be formed. [Means for solving the problem]
[0006] According to the present invention, the above object is to [1] A resin material comprising an EVOH oligomer having a lactone ring at its terminal and having a molecular weight in the range of 300 to 1,500, the content of the EVOH oligomer being 0.003 mass% or more; [2] The resin material according to [1], wherein the content of the ethylene units in the EVOH oligomer is 20 mol % or more and 60 mol % or less based on the total content of the ethylene units and the vinyl alcohol units; [3] The resin material according to [1] or [2], wherein the EVOH oligomer has only ethylene units and vinyl alcohol units as structural units other than the terminal units; [4] The resin material according to any one of [1] to [3], further comprising a thermoplastic resin, the content of the EVOH oligomer being 0.003% by mass or more and 80% by mass or less; [5] The resin material according to [4], wherein the thermoplastic resin is at least one selected from the group consisting of EVOH and polyolefin; [6] The resin material according to [4], wherein the thermoplastic resin is EVOH; [7] The resin material according to any one of [1] to [6], wherein the content of the EVOH oligomer is 10% by mass or more; [8] A compatibilizer containing an EVOH oligomer having a lactone ring at its terminal and a molecular weight in the range of 300 to 1,500; [9] A multilayer structure having a layer formed from any one of the resin materials described in [1] to [7];
[10] The multilayer structure of [9], further comprising a layer containing an adhesive resin as a main component;
[11] The multilayer structure according to [9] or
[10] , wherein the content of the EVOH oligomer in the entire multilayer structure is 0.001% by mass or more and 10% by mass or less;
[12] A method for recycling a multilayer structure, comprising: a step of melt-molding a recovered resin composition containing a recovered multilayer structure having a layer containing a thermoplastic resin and a layer containing an adhesive resin as a main component, wherein the recovered resin composition contains an EVOH oligomer having a lactone ring at an end and having a molecular weight in the range of 300 to 1,500, and the content of the EVOH oligomer in the recovered resin composition is 0.0005% by mass or more and 5% by mass or less; This is achieved by providing either Effect of the Invention
[0007] According to the present invention, it is possible to provide a resin material and a compatibilizer capable of improving the recoverability of a multilayer structure, as well as a multilayer structure having improved recoverability and a method for reusing the multilayer structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] <Resin materials> The resin material of the present invention contains an EVOH oligomer (hereinafter also referred to as "EVOH oligomer (A)") having a lactone ring at an end and a molecular weight in the range of 300 to 1,500, and the content of EVOH oligomer (A) is 0.003 mass% or more.
[0009] The resin material of the present invention can improve the recoverability of the multilayer structure. The reason is unclear, but the following reason is presumed. For example, in a conventional multilayer structure having a general EVOH layer and an adhesive resin layer, when the multilayer structure is recovered and melt-molded, the hydroxyl group of the EVOH and the functional group of the adhesive resin (e.g., acidic group such as carboxyl group or carboxylic anhydride group) react with each other to form a crosslinked resin with a very large molecular weight, which causes gelation. This is thought to be the cause of fish eyes and the like in the recovered layer. In contrast, in the case of a multilayer structure in which the resin material of the present invention is used in at least one layer of the multilayer structure, when the multilayer structure is recovered and melt-molded, the lactone ring at the end of the EVOH oligomer (A) reacts with the functional group of the adhesive resin, which consumes the functional group of the adhesive resin. Therefore, in a multilayer structure having a layer using the resin material, when the multilayer structure is recovered and melt-molded, the formation of a crosslinked resin with a very large molecular weight is suppressed. In addition, the same effect can be obtained by adding the resin material when the conventional multilayer structure is recovered and melt-molded. In other words, the EVOH oligomer (A) can function as a compatibilizer that suppresses the crosslinking reaction between the adhesive resin and other resins and enhances the compatibility between the adhesive resin and other resins when the multilayer structure is recovered and melt-molded. On the other hand, when a high-molecular-weight EVOH having a lactone ring at the end is used instead of the EVOH oligomer (A), the transparency of the recovered layer tends to decrease. For the above reasons, it is presumed that the resin material can improve the recoverability of the multilayer structure. In addition, in the resin material, the EVOH oligomer (A) functions as a compatibilizer, so that the layer formed from the resin material, the recovered layer containing the resin material, etc. can exhibit good gas barrier properties, etc.
[0010] The resin material of the present invention may be in the form (I) of further containing a thermoplastic resin (B) and a relatively small amount of EVOH oligomer (A), or in the form (II) of containing a relatively large amount of EVOH oligomer (A).
[0011] The resin material of form (I) can be suitably used as a melt molding material (thermoplastic resin layer forming material) for forming a thermoplastic resin layer of a multilayer structure or the like. The resin material of form (II) can be suitably used as a compatibilizer or the like to be added to other thermoplastic resins, recycled materials of multilayer structures, or the like. A thermoplastic resin layer, recycled layer, or the like in a multilayer structure can be formed using a thermoplastic resin or recycled materials to which the resin material of form (II) has been added. However, the resin material of form (I) may be used as a compatibilizer or the like, and the resin material of form (II) may be used as a melt molding material or the like. The resin material of the present invention may further contain other components other than the EVOH oligomer (A) and the thermoplastic resin (B). Each component in the resin material will be described in detail below.
[0012] (EVOH Oligomer (A)) The EVOH oligomer (A) is an oligomer having an ethylene unit and a vinyl alcohol unit. In general, EVOH is obtained by a saponification reaction of an ethylene-vinyl ester copolymer. The EVOH oligomer (A) may further have a remaining vinyl ester unit. That is, the EVOH oligomer (A) is a copolymer having an ethylene unit and a vinyl alcohol unit, and further having or not having a vinyl ester unit as an optional monomer unit, and having a molecular weight of 300 to 1,500. The production and saponification of the ethylene-vinyl ester copolymer can be carried out by a known method. Examples of the vinyl ester include vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, vinyl versatate, etc., and vinyl acetate is preferred.
[0013] The EVOH oligomer (A) has a lactone ring at its terminal. The EVOH oligomer (A) preferably has a lactone ring at only one terminal. The number of ring members of the lactone ring is not particularly limited, and may be, for example, a 4- to 6-membered ring, and is preferably a 5-membered ring.
[0014] When the EVOH oligomer (A) has a lactone ring only at one end, the structure of the other end is preferably an ethyl group (-CH2CH3), a 1-hydroxyethyl group (-CH(OH)-CH3) or a 2-hydroxyethyl group (-CH2-CH2(OH)).
[0015] The lactone ring at the end of the EVOH oligomer (A) is formed by chain transfer of the vinyl ester. Specifically, during radical copolymerization of ethylene and vinyl ester, polymerization may be terminated by chain transfer. Then, the polymerization end at this time reacts with a nearby hydroxyl group generated by saponification reaction, forming a lactone ring at the end. Therefore, by carrying out radical copolymerization of ethylene and vinyl ester under conditions that facilitate chain transfer, it becomes easy to obtain an EVOH oligomer (A) having a lactone ring at the end. For example, when ethanol is used as a solvent during copolymerization, ethanol can function as a chain transfer agent. Therefore, when the polymerization reaction is carried out in an environment with a high ratio of ethanol to monomer, it becomes easy to obtain an EVOH oligomer (A) having a lactone ring at the end. In addition, after obtaining EVOH of various molecular weights having lactone rings at the end through the saponification reaction, hot water (for example, hot water of about 80°C) is used to extract oligomer components that are relatively easily dissolved in hot water from this EVOH, and an EVOH oligomer (A) having a lactone ring at the end can be obtained.
[0016] The EVOH oligomer (A) has a molecular weight in the range of 300 to 1,500. This molecular weight is not an average molecular weight but an absolute molecular weight of each molecule. For example, when an EVOH having a lactone ring at the end and a molecular weight distribution in the range of 100 to 100,000 is present, the component having a molecular weight of 300 to 1,500 corresponds to the EVOH oligomer (A). When the molecular weight of the EVOH oligomer (A) is less than 300, the gas barrier properties of the layer formed from the resin material of the present invention tend to decrease. When the molecular weight of the EVOH oligomer (A) is more than 1,500, the compatibility with other thermoplastic resins (e.g., polyethylene, polypropylene, etc.) tends to decrease.
[0017] The peak top molecular weight of the EVOH oligomer (A) is preferably from 500 to 700, and more preferably from 550 to 650. By using the EVOH oligomer (A) having such a peak top molecular weight, the recoverability of the multilayer structure can be further improved.
[0018] The molecular weight distribution (molecular weight distribution curve) and peak top molecular weight of the EVOH oligomer (A) can be determined in terms of polymethyl methacrylate by gel permeation chromatography (GPC) measurement using hexafluoroisopropanol (hereinafter referred to as "HFIP") as a mobile phase and a differential refractive index detector. More specifically, the following method can be adopted. GPC column: Showa Denko K.K.'s "GPC HFIP-806M" Mobile phase: HFIP Flow rate: 1.0mL / min Sample concentration: 0.100wt / vol% Sample injection volume: 100 μL Detector: Differential refractive index detector (VISCOTECH's "TDA305") and an ultraviolet-visible absorbance detector (VISCOTECH's "UV Detector2600") Standard: Polymethylmethacrylate (e.g., Agilent Technologies' "EasiVial PMMA 4mL tri-pack")
[0019] The content of ethylene units in the EVOH oligomer (A) relative to the total of ethylene units and vinyl alcohol units (hereinafter also referred to as "ethylene content") is preferably 20 mol% to 60 mol%, more preferably 30 mol% to 55 mol%, and even more preferably 35 mol% to 50 mol%. When the ethylene content of the EVOH oligomer (A) is within the above range, the recoverability of the multilayer structure can be further improved.
[0020] The lower limit of the saponification degree of the EVOH oligomer (A) is preferably 90 mol%, more preferably 95 mol%, and even more preferably 99 mol%. The upper limit of the saponification degree of the EVOH oligomer (A) may be 100 mol%.
[0021] The EVOH oligomer (A) preferably has only ethylene units and vinyl alcohol units as structural units constituting the structures other than the terminal structures, which refer to terminal groups containing lactone rings and monovalent groups (terminal groups) such as the above-mentioned ethyl group, 1-hydroxyethyl group, 2-hydroxyethyl group, etc.
[0022] The EVOH oligomer (A) preferably has substantially no carboxy groups, more preferably has no carboxy groups, and also preferably has no structural units containing carboxy groups.
[0023] The molar ratio of the terminal group containing a lactone ring to all structural units (terminal structures and other structural units) in the EVOH oligomer (A) is, for example, preferably from 0.1 to 0.2, more preferably from 0.12 to 0.16.
[0024] The EVOH oligomer (A) may have other structural units than the ethylene unit, the vinyl alcohol unit and the vinyl ester unit, within a range that does not impair the effects of the present invention. The upper limit of the content of the other structural units relative to the total structural units of the EVOH oligomer (A) is preferably 30 mol%, more preferably 20 mol%, and may be 10 mol%, 5 mol%, or 1 mol%. In addition, when the EVOH oligomer (A) has the other structural units, the lower limit of the content thereof may be 0.05 mol%, or may be 0.1 mol%.
[0025] Examples of monomers which provide other structural units include unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, etc., or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile, methacrylonitrile, etc.; amides such as acrylamide, methacrylamide, etc.; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, methallylsulfonic acid, etc., or their salts; vinyl silane compounds such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxy-ethoxy) silane, γ-methacryloxypropyl methoxy silane, etc.; alkyl vinyl ethers, vinyl ketones, N-vinyl pyrrolidone, vinyl chloride, vinylidene chloride, etc.
[0026] The other structural unit may be at least one of a structural unit (I) represented by the following formula (I), a structural unit (II) represented by the following formula (II), and a structural unit (III) represented by the following formula (III).
[0027] [ka]
[0028] In formulas (I) to (III), R 1 ~R 11 R are each independently a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms, an alicyclic hydrocarbon group having 3 to 10 carbon atoms, an aromatic hydrocarbon group having 6 to 10 carbon atoms, or a hydroxyl group. 1 , R 2 and R 3 One pair of R 4 and R 5 , or R 6 and R 7 may be bonded (provided that R 1 , R 2 and R 3 One pair of R 4 and R 5 , or R 6 and R 7are both hydrogen atoms). Some or all of the hydrogen atoms in the aliphatic hydrocarbon group having 1 to 10 carbon atoms, the alicyclic hydrocarbon group having 3 to 10 carbon atoms, and the aromatic hydrocarbon group having 6 to 10 carbon atoms may be substituted with a hydroxyl group, an alkoxy group, a carboxyl group, or a halogen atom. R 12 and R 13 are each independently a hydrogen atom, a formyl group, or an alkanoyl group having 2 to 10 carbon atoms.
[0029] When the EVOH oligomer (A) has the structural unit (I), (II) or (III), the flexibility and processability of the resin material of the present invention tend to be improved, and the stretchability, thermoformability, etc. of the resulting multilayer structure, etc. tend to be good.
[0030] In the structural unit (I), (II) or (III), examples of the aliphatic hydrocarbon group having 1 to 10 carbon atoms include an alkyl group, an alkenyl group, etc. Examples of the alicyclic hydrocarbon group having 3 to 10 carbon atoms include a cycloalkyl group, a cycloalkenyl group, etc. Examples of the aromatic hydrocarbon group having 6 to 10 carbon atoms include a phenyl group, etc.
[0031] In the structural unit (I), R 1 , R 2 and R 3 are preferably each independently a hydrogen atom, a methyl group, an ethyl group, a hydroxyl group, a hydroxymethyl group, or a hydroxyethyl group, and among these, from the viewpoint of further improving the stretchability and thermoformability of the resulting multilayer structure or the like, they are more preferably each independently a hydrogen atom, a methyl group, a hydroxyl group, or a hydroxymethyl group.
[0032] The method for incorporating the structural unit (I) into the EVOH oligomer (A) is not particularly limited, and examples thereof include a method of copolymerizing a monomer derived from the structural unit (I) in the polymerization of ethylene and a vinyl ester. Examples of monomers derived from the structural unit (I) include alkenes such as propylene, butylene, pentene, and hexene; 3-hydroxy-1-propene, 3-acyloxy-1-propene, 3-acyloxy-1-butene, 3-hydroxy-1-butene, 4-hydroxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-hydroxy-1-butene, 4-acyloxy-3-hydroxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-hydroxy-1-pentene, 5 ... Examples of alkenes having a hydroxyl group or an ester group include 4,5-hydroxy-1-pentene, 4,5-dihydroxy-1-pentene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-hydroxy-3-methyl-1-pentene, 5-hydroxy-3-methyl-1-pentene, 4,5-dihydroxy-3-methyl-1-pentene, 5,6-dihydroxy-1-hexene, 4-hydroxy-1-hexene, 5-hydroxy-1-hexene, 6-hydroxy-1-hexene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-hexene, and 5,6-diacyloxy-1-hexene. Among them, from the viewpoints of copolymerization reactivity, processability of the resulting multilayer structure, etc., and gas barrier properties, propylene, 3-acyloxy-1-propene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, or 3,4-diacyloxy-1-butene is preferred. As the "acyloxy", acetoxy is preferred, and specifically, 3-acetoxy-1-propene, 3-acetoxy-1-butene, 4-acetoxy-1-butene, or 3,4-diacetoxy-1-butene is preferred. In the case of an alkene having an ester, it is derived into the structural unit (I) during the saponification reaction.
[0033] In the structural unit (II), R4 and R 5 It is preferable that both are hydrogen atoms. 4 and R 5 are both hydrogen atoms, and the above R 6 and R 7 It is more preferable that one of R is an aliphatic hydrocarbon group having 1 to 10 carbon atoms, and the other is a hydrogen atom. The aliphatic hydrocarbon group is preferably an alkyl group or an alkenyl group. From the viewpoint of placing special importance on the gas barrier property of the resulting multilayer structure, etc., 6 and R 7 It is more preferable that one of the R 6 and R 7 One of them is (CH2) h It is more preferable that the substituent is represented by OH (wherein h is an integer of 1 to 8), and the other is a hydrogen atom. Note that h is preferably an integer of 1 to 4, more preferably 1 or 2, and further preferably 1.
[0034] The method for incorporating the structural unit (II) into the EVOH oligomer (A) is not particularly limited, and a method of reacting a monofunctional epoxy compound with an EVOH oligomer obtained by a saponification reaction, etc. is used. As the monofunctional epoxy compound, the compounds represented by the following formulas (IV) to (X) are preferably used.
[0035] [ka]
[0036] In the above formula, R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a hydrogen atom, an aliphatic hydrocarbon group having 1 to 10 carbon atoms (such as an alkyl group or an alkenyl group), an alicyclic hydrocarbon group having 3 to 10 carbon atoms (such as a cycloalkyl group or a cycloalkenyl group), or an aliphatic hydrocarbon group having 6 to 10 carbon atoms (such as a phenyl group). In addition, i, j, k, p, and q each independently represent an integer of 1 to 8. However, R 17is a hydrogen atom, R 18 has a substituent other than a hydrogen atom.
[0037] Examples of the monofunctional epoxy compound represented by formula (IV) include epoxyethane (ethylene oxide), epoxypropane, 1,2-epoxybutane, 2,3-epoxybutane, 3-methyl-1,2-epoxybutane, 1,2-epoxypentane, 3-methyl-1,2-epoxypentane, 1,2-epoxyhexane, 2,3-epoxyhexane, 3,4-epoxyhexane, 3-methyl-1,2-epoxyhexane, 3-methyl-1,2-epoxyheptane, 4-methyl-1,2-epoxyheptane, 1,2-epoxyoctane, 2,3-epoxyoctane, 1,2-epoxynonane, 2,3-epoxynonane, 1,2-epoxydecane, 1,2-epoxydodecane, epoxyethylbenzene, 1-phenyl-1,2-epoxypropane, 3-phenyl-1,2-epoxypropane, etc. Examples of the monofunctional epoxy compound represented by formula (V) include various alkyl glycidyl ethers, etc. Examples of the monofunctional epoxy compound represented by formula (VI) include various alkylene glycol monoglycidyl ethers. Examples of the monofunctional epoxy compound represented by formula (VII) include various alkenyl glycidyl ethers. Examples of the monofunctional epoxy compound represented by formula (VIII) include various epoxy alkanols such as glycidol. Examples of the monofunctional epoxy compound represented by formula (IX) include various epoxy cycloalkanes. Examples of the monofunctional epoxy compound represented by formula (X) include various epoxy cycloalkenes.
[0038] Among the monofunctional epoxy compounds, epoxy compounds having 2 to 8 carbon atoms are preferred. In particular, from the viewpoints of ease of handling and reactivity, the number of carbon atoms in the monofunctional epoxy compound is more preferably 2 to 6, and even more preferably 2 to 4. Furthermore, the monofunctional epoxy compound is particularly preferably a compound represented by formula (IV) or formula (V). From the viewpoints of reactivity, processability of the resulting multilayer structure, gas barrier properties, and the like, 1,2-epoxybutane, 2,3-epoxybutane, epoxypropane, epoxyethane, or glycidol are preferred, and among these, epoxypropane or glycidol is more preferred.
[0039] In the structural unit (III), R 8 , R 9 , R 10 and R 11 is preferably a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and more preferably a methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, tert-butyl group or n-pentyl group.
[0040] The method for incorporating the structural unit (III) into the EVOH oligomer (A) is not particularly limited, and examples thereof include the method described in JP-A-2014-034647.
[0041] The EVOH oligomer (A) may be used alone or in combination of two or more kinds.
[0042] The lower limit of the content of the EVOH oligomer (A) in the resin material of the present invention is 0.003% by mass, and may be 0.01%, 0.1%, 1%, 5%, 10%, 30%, 50%, 70%, or 90% by mass. The upper limit of the content of the EVOH oligomer (A) may be 100% by mass, or may be 80%, 70%, 60%, 50%, 40%, 30%, 25%, 20%, 15%, 10%, 5%, or 3% by mass.
[0043] In the case where the resin material of the present invention further contains a thermoplastic resin (B) and is in the form (I) of, for example, a melt molding material, the content of the EVOH oligomer (A) may be, for example, 0.001% by mass or more and 80% by mass or less, but is preferably 0.04% by mass or more and 70% by mass or less, more preferably 0.1% by mass or more and 40% by mass or less, even more preferably 0.15% by mass or more and 20% by mass or less, and even more preferably 0.3% by mass or more and 5% by mass or less. By setting the content of the EVOH oligomer (A) to the above lower limit or more, recovery is improved, and unevenness in the thickness of the layer when forming a multilayer structure or the like is suppressed, and transparency also tends to be improved. It is presumed that the reason why unevenness in the thickness of the layer is suppressed by the high content of the EVOH oligomer (A) is that the lactone ring present at the end of the EVOH oligomer (A) reacts with the functional group of the adjacent layer (for example, a carboxy group in a layer mainly composed of an adhesive resin) to increase the adhesion with the adjacent layer, thereby increasing the interfacial stress and reducing the unevenness in the thickness. In addition, by setting the content of the EVOH oligomer (A) to the above upper limit or less, the gas barrier properties of the formed layer, multilayer structure, molded article, etc. tend to be improved.
[0044] On the other hand, when the resin material of the present invention contains a relatively large amount of EVOH oligomer (A), for example in the form (II) as a compatibilizer, the content of EVOH (A) may be, for example, from 10 mass% to 100 mass% or from 50 mass% to 99.99 mass%, but is preferably from 85.0 mass% to 99.9 mass%, more preferably from 95.0 mass% to 99.8 mass%, and even more preferably from 99.0 mass% to 99.7 mass%.
[0045] The resin material according to one embodiment of the present invention may have a maximum value in a differential molecular weight distribution curve in a molecular weight range of not less than 300 and not more than 1,500. The differential molecular weight distribution curve can be obtained by GPC measurement.
[0046] (Thermoplastic resin (B)) In one embodiment, the resin material of the present invention preferably contains a thermoplastic resin (B), and more preferably contains a thermoplastic resin as a main component. In this specification, the term "main component" refers to a component whose content is 50% by mass or more. In addition, the EVOH oligomer (A) does not fall under the category of the thermoplastic resin (B). In other words, the thermoplastic resin (B) is a thermoplastic resin other than the EVOH oligomer (A).
[0047] The thermoplastic resin (B) is preferably a thermoplastic resin (B1) that does not substantially have an acidic group. The thermoplastic resin does not substantially have an acidic group means that the content of structural units containing an acidic group relative to the total structural units contained in the thermoplastic resin is 1 mol% or less, preferably 0.1 mol% or less, and more preferably 0 mol%. When the thermoplastic resin has an acidic group, the lactone ring of the EVOH oligomer (A) reacts with the acidic group of the thermoplastic resin, and therefore reacts with the functional group of the adhesive resin, and the effect of the EVOH oligomer (A) of consuming the functional group of the adhesive resin may be difficult to be achieved.
[0048] Examples of the thermoplastic resin (B1) substantially free of acidic groups include polyethylene (linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, etc.), polypropylene, propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymer, polybutene, polypentene, ethylene-vinyl acetate copolymer, EVOH (excluding EVOH oligomer (A)), and other olefin homopolymers, copolymers of multiple olefins, or copolymers of olefins and other monomers; polyesters such as polyethylene terephthalate; polyamides such as nylon-6 and nylon-66; polystyrene, polyvinyl chloride, polyvinylidene chloride, acrylic resins, vinyl ester resins, polyurethane elastomers, polycarbonate, chlorinated polyethylene, chlorinated polypropylene, etc. Among these, olefin homopolymers, copolymers of multiple olefins, or copolymers of olefins and other monomers are preferred, and polyethylene, polypropylene, or EVOH are more preferred.
[0049] The thermoplastic resin (B) may be EVOH (B2). When the thermoplastic resin (B) is EVOH (B2), the layer formed from the resin material of the present invention, the recovery layer containing the resin material, etc. can exhibit particularly good gas barrier properties, transparency, etc. When the thermoplastic resin (B) is EVOH (B2), the dispersibility of the EVOH oligomer (A) in the layer formed from the resin material can be increased, etc. The EVOH (B2) as the thermoplastic resin (B) is preferably an EVOH having a molecular weight of more than 1,500. The EVOH (B2) preferably does not substantially have an acidic group. The EVOH (B2) may or may not have a lactone group at the terminal. The EVOH (B2) can be a conventionally known EVOH.
[0050] The ethylene content in EVOH (B2) is preferably 10 mol% or more and 60 mol% or less, more preferably 20 mol% or more and 55 mol% or less, and even more preferably 25 mol% or more and 50 mol% or less. By making the ethylene content equal to or more than the lower limit, thermal stability and the like tend to be improved. In addition, by making the ethylene content equal to or less than the lower limit, oxygen barrier properties and the like tend to be improved.
[0051] The lower limit of the saponification degree of EVOH (B2) is preferably 90 mol%, more preferably 95 mol%, and even more preferably 99 mol%. By making the saponification degree of EVOH (B2) equal to or higher than the above lower limit, the melt moldability and the gas barrier property of the resulting multilayer structure tend to be good. The upper limit of the saponification degree of EVOH (B2) may be 100 mol%.
[0052] EVOH (B2) may have other structural units than ethylene units, vinyl alcohol units and vinyl ester units, within the range that does not impair the effects of the present invention. The upper limit of the content of other structural units relative to the total structural units of EVOH (B2) is preferably 30 mol%, more preferably 20 mol%, and may be 10 mol%, 5 mol% or 1 mol%. In addition, when EVOH (B2) has the above other structural units, the lower limit of the content may be 0.05 mol% or 0.1 mol%. The monomers that give the other structural units of EVOH (B2) are the same as those given as the monomers that give the other structural units of EVOH oligomer (A).
[0053] The thermoplastic resin (B) may be a polyolefin (B3). The polyolefin (B3) may be a homopolymer of an olefin or a copolymer of multiple kinds of olefins. The polyolefin (B3) may be a homopolymer of an olefin or a copolymer of multiple kinds of olefins among the resins exemplified as the thermoplastic resin (B1), and polyethylene or polypropylene is preferred. The thermoplastic resin (B) and the polyolefin (B3) may be an adhesive resin such as an acid-modified polyolefin.
[0054] The content of the thermoplastic resin (B) in the resin material according to one embodiment of the present invention is preferably 30% by mass or more and 99.96% by mass or less, more preferably 60% by mass or more and 99.9% by mass or less, even more preferably 80% by mass or more and 99.85% by mass or less, and even more preferably 95% by mass or more and 99.7% by mass or less. When the content of the thermoplastic resin (B) is within the above range, the resin material can be particularly suitably used as a layer of a multilayer structure and a melt molding material for other molded products.
[0055] The total content of the EVOH oligomer (A) and the thermoplastic resin (B) in the resin material of the present invention is preferably 90% by mass or more and 100% by mass or less, more preferably 99% by mass or more and 100% by mass or less, and may be 99.9% by mass or more and 100% by mass or less. When the total content of the EVOH oligomer (A) and the thermoplastic resin (B) is within the above range, it is possible to further improve the recoverability of the multilayer structure while exhibiting good functions as a melt molding material, etc.
[0056] (Other Ingredients) The resin material of the present invention may contain other components such as resins other than the EVOH oligomer (A) and the thermoplastic resin (B), metal ions, acids, boron compounds, antioxidants, plasticizers, fillers, antiblocking agents, lubricants, stabilizers, surfactants, colorants, UV absorbers, antistatic agents, drying agents, crosslinking agents, reinforcing materials, etc. Among these, from the viewpoints of thermal stability and adhesion to other resins, it is preferable to contain one or more of metal ions, acids, and boron compounds.
[0057] As the metal ion, an alkali metal ion is preferred because it can enhance the interlayer adhesion when the resin material of the present invention is used as a multilayer structure, and an alkaline earth metal ion is preferred from the viewpoint of thermal stability. These metal ions may exist in the form of a salt.
[0058] When the resin material of the present invention contains such metal ions, the lower limit of the content is preferably 1 ppm, more preferably 5 ppm, even more preferably 10 ppm, even more preferably 20 ppm, and particularly preferably 40 ppm. The upper limit of the content of the metal ions is preferably 3,000 ppm, more preferably 1,000 ppm, even more preferably 500 ppm, and particularly preferably 300 ppm. When the content of the metal ions is within the above range, the interlayer adhesion of the multilayer structure is maintained good, and the thermal stability when the multilayer structure is recovered and reused tends to be good.
[0059] As the acid, carboxylic acid or phosphoric acid is preferable from the viewpoint of increasing the thermal stability during melt molding. As the carboxylic acid, formic acid, acetic acid, butyric acid, lactic acid, etc. are mentioned. As the carboxylic acid, carboxylic acid having 4 or less carbon atoms or saturated carboxylic acid is preferable, and acetic acid is more preferable. The acid may be present in the form of a salt or anion.
[0060] When the resin material of the present invention contains a carboxylic acid, the lower limit of the content of the carboxylic acid is preferably 1 ppm, more preferably 10 ppm, and even more preferably 50 ppm. The upper limit of the content of the carboxylic acid is preferably 10,000 ppm, more preferably 1,000 ppm, and even more preferably 500 ppm. When the resin material contains phosphoric acid, the lower limit of the content of the phosphoric acid is preferably 1 ppm, more preferably 10 ppm, and even more preferably 30 ppm in terms of phosphate radical. The upper limit of the content of the phosphoric acid compound is preferably 10,000 ppm, more preferably 1,000 ppm, and even more preferably 300 ppm. When the resin material contains a carboxylic acid or phosphoric acid within the above range, the thermal stability during melt molding tends to be improved.
[0061] The boron compound includes boric acid, borate esters, borates, and boron hydrides.
[0062] When the resin material of the present invention contains a boron compound, the lower limit of the content of the boron compound is preferably 1 ppm, more preferably 10 ppm. The upper limit of the content of the boron compound is preferably 2,000 ppm, more preferably 1000 ppm. When the resin material contains the boron compound within the above range, the thermal stability during melt molding tends to be good.
[0063] The method for producing the resin material of the present invention is not particularly limited, and can be carried out by a conventionally known method. For example, when the resin material contains an EVOH oligomer (A) and a thermoplastic resin (B), the resin material can be obtained by dry blending each component and melt-kneading them with an extruder or the like. Other components can also be mixed by a conventionally known method.
[0064] The resin material of the present invention can be processed into any form such as pellets or powder and used as a melt molding material, a compatibilizer, etc. The resin material is usually in a dry state. The upper limit of the water content relative to the total solid content of the resin material may be preferably 1% by mass, more preferably 0.1% by mass or 0.01% by mass. When the resin material is in a dry state, it can exhibit good melt moldability, etc.
[0065] <Compatibilizer> The compatibilizer of the present invention contains an EVOH oligomer (A) having a lactone ring at its terminal and having a molecular weight in the range of 300 to 1,500. The compatibilizer may contain the EVOH oligomer (A) as a main component. The preferred form of the composition of the compatibilizer is the same as that described as form (II) containing a relatively large amount of EVOH oligomer (A) in the resin material of the present invention.
[0066] The compatibilizer of the present invention functions suitably as a compatibilizer for enhancing the compatibility between a thermoplastic resin and an adhesive resin. The above-mentioned thermoplastic resin may be the thermoplastic resin exemplified as the thermoplastic resin (B) of the resin material of the present invention. In addition, the above-mentioned adhesive resin may be the adhesive resin used in the adhesive resin layer (layer containing an adhesive resin as a main component) that may be included in the multilayer structure of the present invention described later.
[0067] The compatibilizer of the present invention can increase the compatibility between the thermoplastic resin layer and the adhesive resin layer in the multilayer structure, and improve the recoverability of the multilayer structure. For example, when recovering the multilayer structure and melt molding it, the compatibilizer is added to the recovered multilayer structure, and melt molding is performed, thereby forming a recovered layer with few fish eyes and high transparency. The compatibilizer can also be used as an additive to the thermoplastic resin. The thermoplastic resin to which the compatibilizer is added can be suitably used as a material for forming the thermoplastic resin layer in a multilayer structure having a thermoplastic resin layer and an adhesive resin layer.
[0068] <Multilayer structure> The multilayer structure of the present invention has a layer formed from the resin material of the present invention. The layer formed from the resin material may be a recovery layer. The multilayer structure usually has a layer formed from the resin material and a layer composed of other components. The lower limit of the number of layers of the multilayer structure is, for example, 2, or may be 3 or 4. The upper limit of the number of layers is, for example, 1,000, or may be 100 or 20.
[0069] Examples of the layer made of the other components include a layer containing a thermoplastic resin as a main component and having an EVOH oligomer (A) content of less than 0.003% by mass, a layer containing an adhesive resin as a main component, a recovery layer, a paper layer, a woven fabric layer, a nonwoven fabric layer, a metal cotton strip layer, a wood surface layer, and a metal foil layer. Examples of the recovery layer include a layer containing EVOH, a thermoplastic resin other than EVOH, and a carboxylic acid-modified polyolefin. Among these, it is preferable to have a layer containing an adhesive resin as a main component. It is also preferable to have at least one of a layer containing a thermoplastic resin as a main component and having an EVOH oligomer (A) content of less than 0.003% by mass, and a layer containing an adhesive resin as a main component, and it is more preferable to have both of these.
[0070] Examples of the thermoplastic resin in the layer containing a thermoplastic resin as a main component and having an EVOH oligomer (A) content of less than 0.003 mass % include the thermoplastic resins exemplified as the thermoplastic resin (B) in the resin material of the present invention, and are preferably olefin homopolymers, copolymers of multiple types of olefins, or copolymers of olefins and other monomers, and more preferably EVOH, polyethylene, or polypropylene.
[0071] The layer containing a thermoplastic resin as a main component and having an EVOH oligomer (A) content of less than 0.003 mass % may further contain components exemplified as "other components" in the resin material of the present invention.
[0072] The adhesive resin is preferably an acid-modified polyolefin, more preferably a carboxylic acid-modified polyolefin. The carboxylic acid-modified polyolefin is, for example, an olefin polymer having a carboxy group or an anhydride group thereof obtained by chemically bonding an ethylenically unsaturated carboxylic acid or an anhydride thereof to an olefin polymer by addition reaction, graft reaction, or the like.
[0073] Examples of the ethylenically unsaturated carboxylic acid or anhydride thereof include monocarboxylic acid, monocarboxylic acid ester, dicarboxylic acid, dicarboxylic acid monoester, dicarboxylic acid diester, dicarboxylic acid anhydride, etc. Specific examples include maleic acid, fumaric acid, itaconic acid, maleic anhydride, itaconic anhydride, maleic acid monomethyl ester, maleic acid monoethyl ester, maleic acid diethyl ester, fumaric acid monomethyl ester, etc. Among these, dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride are preferred, and maleic anhydride is more preferred.
[0074] Examples of the olefin-based polymer that serves as the base polymer include polyolefins such as low-density, medium-density, or high-density polyethylene, linear low-density polyethylene, polypropylene, and polybutene; copolymers of olefins and comonomers such as ethylene-vinyl acetate copolymers and ethylene-ethyl acrylate copolymers. The comonomers are not particularly limited as long as they are monomers that can be copolymerized with olefins, and examples include vinyl esters and unsaturated carboxylate esters. The olefin-based polymers are preferably linear low-density polyethylene, ethylene-vinyl acetate copolymers having a vinyl acetate content of 5% by mass or more and 55% by mass or less, or ethylene-ethyl acrylate copolymers having an ethyl acrylate content of 8% by mass or more and 35% by mass or less, and more preferably linear low-density polyethylene or ethylene-vinyl acetate copolymers having a vinyl acetate content of 5% by mass or more and 55% by mass or less.
[0075] Carboxylic acid-modified polyolefins are obtained by introducing an ethylenically unsaturated carboxylic acid or its anhydride into an olefin-based polymer through an addition reaction or a graft reaction in the presence of a solvent such as xylene and a catalyst such as a peroxide. The lower limit of the amount of the carboxylic acid or its anhydride added to the olefin-based polymer or the graft amount (modification degree) is preferably 0.01% by mass, more preferably 0.02% by mass, based on the olefin-based polymer. On the other hand, the upper limit of the amount of the added or grafted amount (modification degree) is preferably 15% by mass, more preferably 10% by mass, based on the olefin-based polymer.
[0076] The layer containing an adhesive resin as a main component may further contain the components exemplified as "other components" in the resin material of the present invention.
[0077] In the general layer structure of a multilayer structure, when a layer containing EVOH, which is a thermoplastic resin, as a main component is represented by E (hereinafter also referred to as "layer (E)"), a layer containing a thermoplastic resin other than EVOH as a main component is represented by T (hereinafter also referred to as "layer (T)"), and a layer containing an adhesive resin as a main component is represented by Ad (hereinafter also referred to as "layer "Ad"), structures such as T / E / T, E / Ad / T, and T / Ad / E / Ad / T can be mentioned. Each of these layers may be a single layer or a multilayer. A part or all of the layer (T) may be a recycled layer. In such a multilayer structure, the layer (E) or layer (T) containing 0.003 mass% or more of EVOH oligomer (A) corresponds to the multilayer structure of the present invention. That is, the layer (E) or layer (T) containing 0.003 mass% or more of EVOH oligomer (A) corresponds to the layer formed from the resin material of the present invention. In the multilayer structure of the present invention, the layer formed from the resin material of the present invention may be one layer, or two or more layers.
[0078] For example, in a multilayer structure having a layer structure of T / Ad / E / Ad / T, the layer (E) may be a layer formed from the resin material of the present invention, and at least one of the layers (T) may be a layer formed from the resin material of the present invention. Both the layer (E) and the layer (T) may be layers formed from the resin material of the present invention. From the viewpoints of dispersibility of the EVOH oligomer (A) and compatibility with other resins, it is preferable that the layer (E) is a layer formed from the resin material of the present invention.
[0079] In the multilayer structure according to one embodiment of the present invention, the outer layer may be a layer formed from the resin material of the present invention. In general, when an oligomer is contained in a layer of a multilayer structure, the adhesiveness may decrease. In contrast, when an oligomer is contained in the outer layer, that is, when the outer layer is a layer formed from the resin material of the present invention, the decrease in adhesive strength caused by the oligomer is suppressed.
[0080] The multilayer structure of the present invention has a layer formed from a resin material containing 0.003% by mass or more of EVOH oligomer (A), and therefore has improved recoverability. That is, when the multilayer structure is recovered and melt-molded for reuse, a good quality recovered layer can be formed, specifically, a recovered layer with few fish eyes and high transparency can be formed. In addition, since the multilayer structure uses EVOH oligomer (A) as a compatibilizer-like component, the multilayer structure can also be configured to exhibit good gas barrier properties, etc.
[0081] The content of the EVOH oligomer (A) in the entire multilayer structure of the present invention is preferably 0.001% by mass to 10% by mass, more preferably 0.004% by mass to 4% by mass, even more preferably 0.015% by mass to 2% by mass, and even more preferably 0.03% by mass to 0.5% by mass. By having the content of the EVOH oligomer (A) in the entire multilayer structure within the above range, it is possible to further improve the recoverability while maintaining good gas barrier properties, etc.
[0082] The content of the EVOH oligomer (A) relative to the content of the adhesive resin in the multilayer structure of the present invention is preferably 0.01% by mass to 90% by mass, more preferably 0.05% by mass to 70% by mass, even more preferably 0.2% by mass to 30% by mass, and even more preferably 0.4% by mass to 5% by mass. By setting the content of the EVOH oligomer (A) relative to the content of the adhesive resin in the multilayer structure within the above range, the functional groups of the adhesive resin are sufficiently consumed during melt molding after recovery, and recovery properties can be further improved.
[0083] Methods for obtaining the multilayer structure of the present invention include, for example, coextrusion molding, coextrusion blow molding, coinjection molding, extrusion lamination, coextrusion lamination, dry lamination, solution coating, etc. The multilayer structure obtained by such a method may be further subjected to secondary processing molding after reheating by a method such as vacuum-pressure deep drawing, blow molding, press molding, etc., to obtain a desired molded structure. The multilayer structure may also be uniaxially or biaxially stretched after reheating in a range below the melting point of EVOH by a method such as roll stretching, pantograph stretching, or inflation stretching to obtain a stretched multilayer structure.
[0084] When the multilayer structure of the present invention is a multilayer film or sheet, the average thickness is not particularly limited, and the lower limit may be, for example, 1 μm, 5 μm, or 10 μm, while the upper limit of the average thickness may be, for example, 3 mm, 1 mm, 300 μm, or 100 μm.
[0085] The multilayer structure of the present invention can be used in various applications similar to those of the past. Examples of applications of the multilayer structure include films, sheets, containers (bags, cups, tubes, trays, bottles, paper cartons, etc.), fuel containers, pipes, fibers, food and beverage packaging materials, container packing materials, medical infusion bag materials, tire tube materials, shoe cushioning materials, bag-in-box inner bag materials, organic liquid storage tank materials, organic liquid transport pipe materials, heating hot water pipe materials (floor heating hot water pipe materials, etc.), cosmetic packaging materials, dental care packaging materials, pharmaceutical packaging materials, packaging sub-parts (caps, bag-in-box cock parts, etc.), pesticide bottles, agricultural films (greenhouse films, soil fumigation films), grain storage bags, geomembranes, vacuum insulation board outer bags, wallpaper or decorative boards, gas tanks for hydrogen, oxygen, etc., etc.
[0086] <How to reuse multi-layer structures> The method for recycling a multilayer structure of the present invention includes a step of melt-molding a recovered resin composition containing a recovered multilayer structure having a layer containing a thermoplastic resin and a layer containing an adhesive resin as a main component, the recovered resin composition containing an EVOH oligomer (A) having a lactone ring at an end and having a molecular weight in the range of 300 to 1,500, and the content of the EVOH oligomer (A) in the recovered resin composition is 0.0005% by mass to 5% by mass. According to the method for recycling a multilayer structure, the EVOH oligomer (A) functions as a compatibilizer, improving the recoverability of the multilayer structure and making it possible to form a recovered layer with few fisheyes and high transparency.
[0087] In the method for recycling a multilayer structure of the present invention, the multilayer structure to be recovered may be a conventionally known multilayer structure or may be one of the multilayer structures of the present invention. For example, when the content of EVOH oligomer (A) in the recovered resin composition containing the recovered multilayer structure is less than 0.0005% by mass, the recovered resin composition containing EVOH oligomer (A) in an amount of 0.0005% by mass to 5% by mass may be prepared by adding EVOH oligomer (A), and melt molding may be performed. The content of EVOH oligomer (A) in the recovered resin composition is preferably 0.001% by mass to 4% by mass, more preferably 0.005% by mass to 3.3% by mass, even more preferably 0.008% by mass to 2.8% by mass, and even more preferably 0.015% by mass to 2.5% by mass.
[0088] The content of the EVOH oligomer (A) relative to the content of the adhesive resin in the recovered resin composition to be subjected to melt molding is preferably 0.04% by mass or more and 85% by mass or less, more preferably 0.09% by mass or more and 70% by mass or less, even more preferably 0.15% by mass or more and 60% by mass or less, and even more preferably 0.3% by mass or more and 55% by mass or less. By setting the content of the EVOH oligomer (A) relative to the content of the adhesive resin in the recovered resin composition within the above range, the functional groups of the adhesive resin are sufficiently consumed, and the recoverability can be further improved. EXAMPLES
[0089] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0090] <Synthesis Example 1> Synthesis of EVOH resin (EVOH-A1) containing EVOH oligomer (Oli-A1) A 200L pressurized reactor equipped with a jacket, a stirrer, a nitrogen inlet, an ethylene inlet, and an initiator addition inlet was charged with 75.0 kg of vinyl acetate (hereinafter sometimes referred to as VAc) and 7.2 kg of ethanol (hereinafter sometimes referred to as EtOH), and nitrogen bubbling was performed for 30 minutes to replace the atmosphere in the reactor with nitrogen. Next, the temperature in the reactor was adjusted to 65°C, and then ethylene was introduced so that the reactor pressure (ethylene pressure) was 4.74 MPa, and 9.4 g of 2,2'-azobis(2,4-dimethylvaleronitrile) ("V-65" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added as an initiator to start polymerization. During polymerization, the ethylene pressure was maintained at 4.13 MPa, and the polymerization temperature was maintained at 65°C. After 4 hours, when the conversion rate of VAc (polymerization rate based on VAc) reached 49.7%, the mixture was cooled, and 0.2 g of copper acetate dissolved in 20 kg of methanol (hereinafter sometimes referred to as MeOH) was added to the vessel to terminate the polymerization. The reaction vessel was opened to remove ethylene, and nitrogen gas was bubbled through to completely remove ethylene. The polymerization liquid was then removed from the vessel and diluted with 20 L of MeOH. This liquid was fed from the top of a tower vessel, and MeOH vapor was fed from the bottom of the vessel to remove the unreacted monomers and EtOH remaining in the polymerization liquid together with the MeOH vapor, to obtain a MeOH solution of ethylene-vinyl acetate copolymer (hereinafter sometimes referred to as EVAc). Next, 150 kg of a 20 mass % MeOH solution of EVAc was charged into a 300 L reaction vessel equipped with a jacket, a stirrer, a nitrogen inlet, a reflux condenser, and a solution addition port. The solution was heated to 60°C while blowing nitrogen gas into it, and a MeOH solution with a 2N concentration of sodium hydroxide was added at a rate of 450mL / min for 2 hours. After the addition of the sodium hydroxide MeOH solution was completed, the temperature in the system was kept at 60°C, and the saponification reaction was allowed to proceed for 2 hours while stirring and discharging MeOH and methyl acetate produced by the saponification reaction out of the reaction vessel. Then, 8.7 kg of acetic acid was added to stop the saponification reaction. The obtained crude dried EVOH resin was subjected to heat extraction using hot water and dried to obtain an EVOH resin (EVOH-A1) containing an EVOH oligomer (Oli-A1) having a lactone ring at its end.
[0091] The obtained EVOH resin (EVOH-A1) contained 60% by mass of EVOH oligomer (Oli-A1) having a molecular weight in the range of 300 to 1,500 as a result of GPC measurement. In addition, the peak top molecular weight (Mp) of the EVOH oligomer (Oli-A1) was 606, the weight average molecular weight (Mw) was 1,000, and the number average molecular weight (Mn) was 490 as a result of GPC measurement. In addition, the ethylene content of the EVOH oligomer (Oli-A1) was 43 mol%, and one lactone ring per molecule was at the end. The obtained EVOH resin (EVOH-A1) itself is also an example of the resin material of the present invention. The GPC measurement was performed under the following conditions.
[0092] [GPC measurement] GPC measurements were performed using VISCOTECH's "GPCmax." The molecular weight was calculated based on the signal intensity detected by the differential refractive index detector and the ultraviolet-visible absorbance detector. VISCOTECH's "TDA305" and "UV Detector2600" were used as the differential refractive index detector and the ultraviolet-visible absorbance detector. The absorbance detector had a detection cell with an optical path length of 10 mm. Showa Denko's "GPC HFIP-806M" was used as the GPC column. The analysis software used was "OmniSEC (Version 4.7.0.406)" that came with the device.
[0093] (Measurement conditions) A measurement sample was taken and dissolved in hexafluoroisopropanol (hereinafter referred to as "HFIP") containing 20 mmol / L of sodium trifluoroacetate to prepare a 0.100 wt / vol% solution. For the measurement, a solution filtered through a 0.45 μm polytetrafluoroethylene filter was used. The measurement sample was dissolved by leaving it to stand overnight at room temperature.
[0094] The mobile phase was HFIP containing 20 mmol / L sodium trifluoroacetate. The flow rate of the mobile phase was 1.0 mL / min. The sample injection volume was 100 μL, and the GPC column temperature was 40° C.
[0095] (Creating a calibration curve) As a standard, Agilent Technologies polymethyl methacrylate (hereinafter abbreviated as "PMMA") (peak top molecular weight: 1,944,000, 790,000, 467,400, 271,400, 144,000, 79,250, 35,300, 13,300, 7,100, 1,960, 1,020 or 690) was measured, and a calibration curve was prepared for converting the elution volume to the molecular weight of PMMA for each of the differential refractive index detector and the absorbance detector. The above-mentioned analysis software was used to prepare each calibration curve. In this measurement, a column capable of separating the peaks of standard samples with molecular weights of 1,944,000 and 271,400 was used for the measurement of PMMA.
[0096] <Example 1> (Preparation of resin material (Y1)) 0.033 parts by mass of the EVOH resin (EVOH-A1) obtained in Synthesis Example 1 and 99.967 parts by mass of a general-purpose EVOH (ethylene content 38 mol%) were dry-blended. As described above, the EVOH resin (EVOH-A1) contained 60% by mass of an EVOH oligomer (Oli-A1) having a molecular weight in the range of 300 to 1,500, and the remaining 40% by mass was other EVOH. This dry blend was melt-molded using a twin-screw extruder (two-screw segment extruder "2D30W2" (D (mm) = 25, L / D = 30, screws: same direction fully intermeshing type) manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain pellets of a resin material (Y1). The general-purpose EVOH was "EVAL (trademark) H171B" (density 1.17 g / cm3) manufactured by Kuraray Co., Ltd. 3 ) was used, and this general-purpose EVOH was substantially free of EVOH oligomers having a molecular weight in the range of 300 to 1,500. The composition of the obtained resin material (Y1) is shown in Table 1.
[0097] (Fabrication of multi-layered structures) Using a co-extrusion multi-layer cast film-making device, the PO (polyolefin) layer was made of low-density polyethylene (LDPE; Dow Chemical Company's "LDPE 310E"); density 0.92 / cm 3 ), the barrier layer is made of a resin material (Y1), and the adhesive resin layer is made of maleic anhydride-modified polyethylene ("Admer (trademark) NF518" manufactured by Mitsui Chemicals, Inc., density 0.91 g / cm 3 A multilayer structure (five-layer coextruded multilayer cast film) having a layer thickness and layer structure of PO layer / adhesive resin layer / barrier layer / adhesive resin layer / PO layer=41 μm / 5 μm / 8 μm / 8 μm / 41 μm was produced. The PO layer and barrier layer were both layers whose main component was a thermoplastic resin substantially free of acidic groups. The film production conditions were as follows: (Co-extrusion conditions) Extrusion temperature of PO layer: feeding section / compression section / metering section / die=180 / 220 / 220 / 220℃ Extrusion temperature of barrier layer: feeding section / compression section / metering section / die=180 / 220 / 220 / 220℃ Extrusion temperature of adhesive resin layer: feeding section / compression section / metering section / die=180 / 220 / 220 / 220℃ Extruder: PO layer: 32φ extruder GT-32-A type (manufactured by Plastics Engineering Research Institute Co., Ltd.) Barrier layer: 20φ extruder, lab machine ME type CO-EXT (manufactured by Toyo Seiki Seisakusho Co., Ltd.) Adhesive resin layer: 25φ extruder P25-18-AC type (Osaka Seiki Kogyo Co., Ltd.) T-die: 300mm width, 3 types, 5 layers (manufactured by Plastics Engineering Research Institute Co., Ltd.) Cooling roll temperature: 80℃ Take-off speed: 3.0m / min
[0098] (Gas barrier property evaluation) The obtained multilayer structure was attached to an oxygen transmission rate measuring device, and the oxygen transmission rate was measured by the isobaric method in accordance with JIS K7126-2: 2006. The measurement conditions were as follows: Equipment: MOCON OX-TRAN2 / 21 manufactured by MOCON Temperature: 20℃ Humidity on oxygen supply side: 65% RH Humidity on carrier gas side: 0% RH Carrier gas flow rate: 10mL / min Oxygen pressure: 1.0atm The gas barrier properties were evaluated based on the oxygen permeability according to the following criteria, and the results are shown in Table 2. (standard) A: 2cc / (m 2 ·day·atm) B: 2cc / (m 2 ·day · atm) or more 2.5cc / (m 2 ·day·atm) C: 2.5cc / (m 2 ·day · atm) or more 3cc / (m 2 ·day·atm) D: 3cc / (m 2 ·day · atm) or more
[0099] (Thickness deviation measurement) The cross section of the obtained multilayer structure was cut out using a microtome RX-860 manufactured by Yamato Koki Kogyo Co., Ltd., and observed using an optical microscope manufactured by LEICA. The thickness of the barrier layer was measured at 10 points at equal intervals from the center in the width direction, and the standard deviation was defined as the thickness deviation. The smaller the thickness deviation, the better the appearance of the multilayer structure. The results are shown in Table 2. (standard) A: Less than 10% B: 10% or more but less than 20% C: 20% or more but less than 40% D: 40% or more
[0100] (Transparency evaluation of multi-layered structures) A square sample measuring 10 cm x 10 cm was cut out from the center of the obtained multilayer structure. Next, the haze of the cut sample was measured using a Boyk integrating sphere light transmittance / total light reflectance meter ("HR-100" manufactured by Murakami Color Research Laboratory) in accordance with JIS K7375. The evaluation criteria were as follows. The results are shown in Table 2. (standard) A: Less than 10% B: 10% or more but less than 15% C: 15% or more but less than 20% D: 20% or more
[0101] (Preparation of monolayer film) Except for changing all the resins used in each extruder to low-density polyethylene (LDPE; “LDPE 310E” manufactured by Dow Chemical Company), film production was carried out in the same manner as in the preparation of the multilayer structure described above, and a 100 μm-thick LDPE monolayer film was obtained.
[0102] (Crushing) The multilayer structure obtained above was pulverized in a pulverizer with a diameter of 8 mm to produce a multilayer structure recovered product. The monolayer film obtained above was pulverized in a pulverizer with a diameter of 8 mm to produce a monolayer film recovered product.
[0103] (Preparation of Recycled Resin Composition Pellets) The recovered materials obtained above were dry blended and melt-kneaded to a mass ratio of multilayer structure recovered material / single-layer film recovered material = 50 / 50. The melt-kneading was performed using a Toyo Seiki Seisakusho Co., Ltd. twin-screw segment extruder "2D30W2" (D (mm) = 25, L / D = 30, screws: same direction fully intermeshing type) to a resin temperature of 220°C, and recovered resin composition pellets (cylindrical pellets with a diameter of 2 mm and a length of 4 mm) were obtained. The composition of the recovered resin composition pellets obtained is shown in Table 3.
[0104] (Production of recycled monolayer film) 50 parts by mass of the recovered resin composition pellets obtained above and 50 parts by mass of low-density polyethylene (LDPE; "LDPE 310E" manufactured by The Dow Chemical Company) were dry-blended, and a monolayer film was formed under the following conditions using a 20 mm extruder "D2020" manufactured by Toyo Seiki Seisakusho Co., Ltd. (D (mm) = 20, L / D = 20, compression ratio 3.5, screw: full flight) to obtain a recovered monolayer film. (Extrusion conditions) Extrusion temperature: feeding section / compression section / metering section / die = 180 / 220 / 220 / 220℃ Screw rotation speed: 40 rpm Cooling roll temperature: 50℃ Film thickness: 25μm
[0105] (Transparency evaluation of recycled monolayer film) A 10cm x 10cm square sample was cut out from the center of the recovered monolayer film. The haze of the cut sample was then measured in accordance with JIS K7375 using a Boyk integrating sphere light transmittance / total light reflectance meter ("HR-100" manufactured by Murakami Color Research Laboratory). The evaluation criteria were as follows. The results are shown in Table 3. (standard) A: Less than 9% B: 9% or more but less than 10% C: 10% to less than 12% D: 12% or more
[0106] (Fisheye evaluation) During the preparation of the recovered monolayer film, a defect detector (Frontier Systems' "FE Counter") was used to measure defects of 0.08 m wide x 1 m long (0.08 m 2 The number of fish eyes in the sample was counted. The evaluation criteria were as follows. The results are shown in Table 3. (standard) A: 50 or less fish eyes B: Fisheye count: 51 to 200 C: Fisheye count: 201 to 500 D: 501 or more fish eyes
[0107] <Examples 2 to 8, Comparative Example 2> The resin materials (Y2 to Y8, YC2) of Examples 2 to 3 and Comparative Example 2 were obtained in the same manner as in Example 1, except that the mixing ratio of the EVOH resin (EVOH-A1) obtained in Synthesis Example 1 and a general-purpose EVOH (ethylene content: 38 mol%) when dry blended was set as shown in Table 1. The composition of each of the obtained resin materials is shown in Table 1. A multilayer structure, a monolayer film, recycled resin composition pellets, and a recycled monolayer film were prepared and evaluated in the same manner as in Example 1, except that the type of resin material (Y) was changed as shown in Table 2. The compositions of the obtained recycled resin compositions are shown in Table 3. The results are shown in Tables 2 and 3.
[0108] <Example 9> Instead of the general-purpose EVOH, low-density polyethylene (PO; Dow Chemical Company's "LDPE 310E", density 0.92 / cm 3 A resin material (Y9) of Example 9 was obtained in the same manner as in Example 5, except that ), was used. The composition of the obtained resin material is shown in Table 1. A multilayer structure, a monolayer film, a recovered resin composition pellet, and a recovered monolayer film were produced and evaluated in the same manner as in Example 1, except that the resin material (Y9) was used as the resin material (Y). The composition of the recovered resin composition obtained is shown in Table 3. The results are shown in Tables 2 and 3.
[0109] <Example 10> Instead of the general-purpose EVOH, maleic anhydride-modified polyethylene (Tie; Mitsui Chemicals, Inc. "Admer (trademark) NF518", density 0.91 g / cm 3 A resin material (Y10) of Example 10 was obtained in the same manner as in Example 5, except that ), was used. The composition of the obtained resin material is shown in Table 1. A multilayer structure, a monolayer film, a recovered resin composition pellet, and a recovered monolayer film were produced and evaluated in the same manner as in Example 1, except that the resin material (Y10) was used as the resin material (Y). The composition of the recovered resin composition obtained is shown in Table 3. The results are shown in Tables 2 and 3.
[0110] <Comparative Example 1> General-purpose EVOH (Kuraray Co., Ltd. "EVAL (trademark) H171B" density 1.17 g / cm 3 ) was used as the resin material (YC1) of Comparative Example 1. The composition of the resin material is shown in Table 1. A multilayer structure, a monolayer film, recycled resin composition pellets, and a recycled monolayer film were produced and evaluated in the same manner as in Example 1, except that the resin material (YC1) was used as the resin material (Y). The composition of the recycled resin composition obtained is shown in Table 3. The results are shown in Tables 2 and 3.
[0111] <Comparative Example 3> Low-density polyethylene (PO; Dow Chemical Company "LDPE 310E", density 0.92 / cm 3 ) was used as the resin material (YC3) of Comparative Example 3. A multilayer structure, a monolayer film, recovered resin composition pellets, and a recovered monolayer film were produced and evaluated in the same manner as in Example 1, except that the resin material (YC3) was used as the resin material (Y). The composition of the recovered resin composition obtained is shown in Table 3. The results are shown in Tables 2 and 3.
[0112] <Comparative Example 4> Maleic anhydride modified polyethylene (Tie; Mitsui Chemicals, Inc. "Admer (trademark) NF518", density 0.91 g / cm 3 ) was used as the resin material (YC4) of Comparative Example 4. A multilayer structure, a monolayer film, recycled resin composition pellets, and a recycled monolayer film were produced and evaluated in the same manner as in Example 1, except that the resin material (YC4) was used as the resin material (Y). The composition of the recycled resin composition obtained is shown in Table 3. The results are shown in Tables 2 and 3.
[0113] [Table 1]
[0114] [Table 2]
[0115] [Table 3]
[0116] As shown in Table 3, when a recovered monolayer film was produced using each of the recovered resin compositions obtained by recovering each of the multilayer structures of Examples 1 to 10, a recovered monolayer film with few fish eyes and high transparency could be obtained. Therefore, it was confirmed that each of the resin materials used in Examples 1 to 10 can improve the recoverability of the multilayer structure. Furthermore, as shown in Table 2, each of the multilayer structures of Examples 1 to 8 had good gas barrier properties, small thickness deviation, and transparency. [Industrial Applicability]
[0117] The resin material of the present invention is useful as a molding material for multilayer structures and the like, and as an additive when recovering and reusing multilayer structures.
Claims
1. The present invention comprises an ethylene-vinyl alcohol copolymer oligomer having a lactone ring at its terminal and a molecular weight in the range of 300 to 1,500, The resin material has a content of the ethylene-vinyl alcohol copolymer oligomer of 0.003% by mass or more.
2. 2. The resin material according to claim 1, wherein the content of the ethylene units in the ethylene-vinyl alcohol copolymer oligomer relative to the total of the ethylene units and the vinyl alcohol units is 20 mol % or more and 60 mol % or less.
3. 3. The resin material according to claim 1, wherein the ethylene-vinyl alcohol copolymer oligomer has only ethylene units and vinyl alcohol units as structural units constituting structures other than the terminal structures.
4. Further comprising a thermoplastic resin, The resin material according to any one of claims 1 to 3, wherein the content of the ethylene-vinyl alcohol copolymer oligomer is 0.003% by mass or more and 80% by mass or less.
5. The resin material according to claim 4, wherein the thermoplastic resin is at least one selected from the group consisting of ethylene-vinyl alcohol copolymers and polyolefins.
6. The resin material according to claim 4, wherein the thermoplastic resin is an ethylene-vinyl alcohol copolymer.
7. The resin material according to any one of claims 1 to 6, wherein the content of the ethylene-vinyl alcohol copolymer oligomer is 10 mass% or more.
8. A compatibilizer comprising an ethylene-vinyl alcohol copolymer oligomer having a lactone ring at its terminal and having a molecular weight in the range of 300 or more and 1,500 or less.
9. A multilayer structure having a layer formed from the resin material according to any one of claims 1 to 7.
10. The multilayer structure according to claim 9 , further comprising a layer containing an adhesive resin as a main component.
11. The multilayer structure according to claim 9 or 10, wherein the content of the ethylene-vinyl alcohol copolymer oligomer is 0.001% by mass or more and 10% by mass or less based on the entire multilayer structure.
12. The method includes a step of melt-molding a recovered resin composition including a recovered multilayer structure having a layer containing a thermoplastic resin and a layer containing an adhesive resin as a main component, the recovered resin composition contains an ethylene-vinyl alcohol copolymer oligomer having a lactone ring at its terminal and a molecular weight in the range of 300 to 1,500, The method for recycling a multilayer structure, wherein the content of the ethylene-vinyl alcohol copolymer oligomer in the recovered resin composition is 0.0005% by mass or more and 5% by mass or less.
Citation Information
Patent Citations
Thermoforming multilayered structure and thermoformed container
JP2001058374A